Memory, scene construction, and the human hippocampus - Kim, Soyun (Proc Natl Acad Sci U S A, 2015)
We evaluated two different perspectives about the function of the human hippocampus–one that emphasizes the importance of memory and another that emphasizes the importance of spatial processing and scene construction. We gave tests of boundary extension, scene construction, and memory to patients with lesions limited to the hippocampus or large lesions of the medial temporal lobe. The patients were intact on all of the spatial tasks and impaired on all of the memory tasks. We discuss earlier studies that associated performance on these spatial tasks to hippocampal function. Our results demonstrate the importance of medial temporal lobe structures for memory and raise doubts about the idea that these structures have a prominent role in spatial cognition.